Evolutions of mechanical and thermal properties of TmNbO4/Tm3NbO7 composites as protective coating materials - Jiankun Wang; Lin Chen; Baihui Li; Hao Xu; Xiang Jiang; Jing-Feng Li; Jing Feng (Journal of Advanced Ceramics)
High fracture toughness, low thermal conductivity, and thermal expansion coefficient (TEC) matching substrate are essential for thermal barrier coatings (TBCs) and abradable seal coatings (ASCs). In this work, TmNbO4/Tm3NbO7 composites are designed and synthesized to increase their fracture toughness (KIC) and thermal insulation performance. Compared with those of TmNbO4 (KIC = 2.2±0.1 MPa·m1/2) and Tm3NbO7 (KIC = 1.7±0.2 MPa·m1/2), the increments in fracture toughness are as high as 50.0% and 91.1%, respectively. The highest toughness reaches 3.3±0.4 MPa·m1/2, which is attributed to the superior combination of grains between TmNbO4 and Tm3NbO7, as well as the simultaneous effects of microcracks and crack bridging and bifurcation. Accurate estimation of the effect of the interfacial thermal resistance on the thermal conductivity at low temperatures was achieved using the minimum interfacial thermal resistance model. A novel method is proposed to inhibit radiative heat transfer by utilizing oxides with glass-like thermal conductivity to suppress thermal radiation. Consequently, the TmNbO4/Tm3NbO7 composite maintains a low thermal conductivity (1.19–2.02 W·m−1·K−1) at 1000 °C. The high TECs (10.4×10−6–11.8×10−6·K−1 at 1500 °C) and excellent high-temperature stability ensure that the designed TmNbO4/Tm3NbO7 composites can be used at temperatures reaching 1500 °C. Accordingly, simultaneous enhancement of fracture toughness and thermal insulation in TmNbO4/Tm3NbO7 composites is effective, and the revealed mechanisms are useful for various materials.